Faktor Pengaruh Return Saham Perusahaan Sektor Consumer Goods yang Terdaftar di BEI Periode 2012-2017 - IMAMUDDIN, FADLI; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2019)
This purpose of this research to analyze the effect of the Return on Asset (ROA), Economic Value Added (EVA), Market Value Added (MVA), Stock Liquidity, Growth Opportunities, Idiosyncratic risk, Interest Rate, and Exchange Rate on Stock Returns of consumer goods sector company period 2012-2017. The dependent variable in this research is Stock Returns, while the independent variables include the ROA, EVA, MVA, Stock Liquidity, Growth Opportunities, Idiosyncratic Risk, Interest Rate, and Exchange Rate. The research includes causality research and this type of data is secondary data obtained from yahoo finance, SahamOk, Bank of Indonesia and Indonesia Stock Exchange. This study uses the ratio of changes every year to obtain the sample number is 139. This research use multiplier linier regression analysis method. The result of this research that ROA, EVA, MVA, Stock Liquidity, Growth Opportunities, and Interest Rate have no effect to Stock Returns. Meanwhile Idiosyncratic Risk has a significant positive effect on the Stock Returns and Exchange Rate have a significant negative effect on the Stock Returns. Then all independent variables are simultaneously had effect on Stock Returns. The adjusted R square value 0,114 which means that the movement of Stock Return influenced 11% by the variables on this study and 89% is explained by variables outside this research. Keywords: exchange rate; idiosyncratic risk; stock returns.